Surface factors controlling the volume of accumulated Labrador Sea Water - Kostov, Y; Messias, M-J; Mercier, H; Marshall, D; Johnson, HL (Copernicus Publications, 2024)
We explore historical variability in the volume of Labrador Sea Water (LSW) using ECCO, an ocean state estimate configuration of the Massachusetts Institute of Technology general circulation model (MITgcm). The model’s adjoint, a linearization of the MITgcm, is set up to output the lagged sensitivity of the watermass volume to surface boundary conditions. This allows us to reconstruct the evolution of LSW volume over recent decades using historical surface wind stress, heat, and freshwater fluxes. Each of these boundary conditions contributes significantly to the LSW variability that we recover, but these impacts are associated with different geographical fingerprints and arise over a range of time lags. We show that the volume of LSW accumulated in the Labrador Sea exhibits a delayed response to surface wind stress and buoyancy forcing outside the convective interior of the Labrador Sea, at key locations in the North Atlantic Ocean. In particular, winds and surface density anomalies affect the North Atlantic Current’s (NAC) transport of warm and saline subtropical water masses that are precursors for the formation of LSW. This propensity for a delayed response of LSW to remote forcing allows us to predict a substantial fraction of LSW variability at least a year into the future. Our analysis also enables us to attribute LSW variability to different boundary conditions and to gain insight into the major mechanisms that drive volume anomalies in this deep watermass. We point out the important role of buoyancy loss and preconditioning along the NAC pathway, in the Iceland Basin, the Irminger Sea, and the Nordic Seas, processes which facilitate the formation of LSW both in the Irminger and in the Labrador Sea.